HSE performance report on NSP 2011. November 2011. (Health Service Executive, 2012)
The Performance Report (PR) provides an overall analysis of key performance data from Finance, HR, Hospital and Primary & Community Services. The activity data reported is based on Performance Activity and Key Performance Indicators outlined in the National Service Plan 2011. The PR is used by the Performance Monitoring & Control committee (PMCC), the CEO and the HSE Board to monitor performance against planned activity, as outlined in the NSP, and to highlight areas for improvement. The PR also provides an update to the DoH on the delivery of the NSP. Social Inclusion (p.34, main report) The total number of clients in methadone treatment for the month of October (reported monthly in arrears) was 9,264, of these 527 were in a prison setting. 8,737 were treated in HSE areas (see breakdown below). This compares to 8,681 for the same period last year. Clients treated in HSE Area outside prisons • DML 5,023 • DNE 3,028 • South 387 • West 299 • Prisons 527 • National 9,264 See page 38 of supplementary report for breakdown of figures for methadone treatment activity and substance misuse treatment.